Deposit insurance protection and a financial safety net in need of mending. Lessons learned and the case for further integration, harmonization and rational improvement following the 2008-2009 worldwide financial pandemic - Rabkin, Alan Brent (Trinity College (Dublin, Ireland). School of Law, 2010)
The latest financial crisis has exposed many ongoing deficiencies in the design, implementation and funding of deposit insurance programs in the United States, similar schemes in the European Union, and protective programs around the world. As an important part of the financial safety net, deposit insurance is designed to provide a major part of the package of protections against catastrophic bank failure. However, the financial pandemic of 2008 and 2009 has demonstrated that the programs and schemes worldwide generally remain significantly underpowered and many are obviously deficient and often come to near collapse in the face of Systemic Risk.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin